Relation between cannabidiol use and pain: a bibliographic review (Research, Society and Development, 2023)
Introduction: Pain can be incapacitating depending on its intensity and duration, causing the individual to have a loss in quality of life. Currently, the recommended treatments present beneficial effects that are scarce in the short term and their adverse effects make new pharmacological therapies indispensable. In this sense, the use of Cannabidiol is currently observed. Objective: To analyze the effect of Cannabidiol in individuals with chronic and acute pain. Method: This is an integrative literature review on the effects of Cannabidiol as a treatment for chronic and acute pain. The search will be conducted using the keywords based on the Descriptors in Health Sciences (DeCS) in the Portuguese languages: Cannabidiol, Pain, Chronic Pain, Acute Pain, Neuropathies.  At the end of the project, it will use the PRISMA Protocol for the articles to be selected. Results: The work evidenced predominantly positive results regarding the use of cannabidiol (CBD) for pain management. Overall, in the analyzed studies, the cannabis-derived compound showed good efficacy in antinociceptive effects in the observed individuals. Conclusion: the use of cannabidiol for pain management is a promising therapy, but still needs more understanding about its prolonged use and mechanisms of action.